Endoscopic Transnasal Dacryocystorhinostomy: Our Experience And Case Series Analysis - Khalid Hussain Mahida; Muhammad Ayub; Qurat- (ziauddin University, 2024)
Background: This study aims to describe our surgical technique and results for endoscopic transnasal dacryocystorhinostomy for the blocked nasolacrimal passage in patients presented in the department of Otolaryngology and ophthalmology at a tertiary care center. Methods: A consecutively presenting case series of blocked nasolacrimal passage were selected for transnasal endoscopic dacryocystorhinostomy. Bone removal done by cold instruments and the drill was used to remove the bone over the superior aspect of the sac. Medial wall of the sac was removed to marsupialize the sac in the nasal cavity. Septoplasty was done in 13 patients (17.10 %). The specific surgical approach with or without septoplasty and the use of endolight was discussed. Postoperative follow up including endoscopic examination and results are documented. Results: A total of 76 cases were included. Mean age was 37.32 (range 6-76)). An endolight was used in all cases to localize the site of nasolacrimal sac72 cases (94.74 %) have successful outcome in terms of relief of symptoms, whereas 4(5.26 %) cases had persistent epiphora. Revision procedure were done and 3(3/4, 75 %) cases had successful outcome. The overall success rate in our series of primary and revision ETDCR is 98.68 %. Conclusion: Endoscopic transnasal dacryocystorhinostomy is an effective treatment for nasolacrimal duct obstruction. Use of the endolight to localize and the power drill to expose the sac and septoplasty; contribute to the ultimate surgical success Key Words: Dacryocystorhinostomy, Nasoendoscopy, Dacryocystitis, Epiphora